Funcionamiento y estado de salud en una población de amputados de miembro inferior en Medellín, Colombia (2016)
ABSTRACT: General objective: To describe a measure of the functioning and perceived health status among lower limb amputees in Medellín, Colombia. Methodology: Cross-sectional study to assess functioning with the WHO-DAS and health status with the EQ-5D in patients with lower limb amputation. Results: 154 patients were interviewed. The mobility domain of the WHO-DAS was the most affected in amputees over the knee (average: 21.66; DE: 17.61) and under the knee (average: 25.77; DE: 22.89). There were significant differences only according to the time since the amputation. In the EQ-5D, the average utility weight value was 0.821 among those with 5 years or less since amputation, and 0.920 (p = 0.022) in those amputated more than 10 years before. Results of health perception on the visual analog scale showed similar and statistically significant differences. Conclusion: In the analyzed sample, functioning and quality of life are more associated with time since amputation than with the level or etiology of this intervention.